Photodegradation kinetics of Bilastine in tablets - Machado, Ariele Nunes; Erd, Jéssica Resch; Silva, Andressa Tassinari da; Brabo, Gabriela Rossi; Portela, José Luiz Ribeiro; Bajerski, Lisiane; Paim, Clésio Soldateli (Drug Analytical Research, 2026)
Photodegradation is the process by which a chemical substance is broken down through exposure to light, typically ultraviolet (UV) radiation. This process is significant in environmental chemistry, where sunlight can degrade pollutants and materials, influencing their persistence and toxicity. Bilastine is a novel non-sedating histamine H1-receptor antagonist developed for the treatment of allergic rhino conjunctivitis and urticaria. The literature presents some studies on the quantitative determination of bilastine by high-performance liquid chromatography in pharmaceutical forms and biological fluids, however, no data on the photodegradation kinetics of this drug are described. Therefore, the objective of the study was to determine the photodegradation kinetics of the drug bilastine in coated tablets using a liquid chromatography method previously developed and validated by the same research group (unplished data). The study was carried out with methanolic solution containing 100.0 mg mL-1 of bilastine drug product exposed to UV-C radiation (254 nm). The irradiation of the samples was done at pre-established times: 0, 15, 30, 60, 120 and 180 minutes. The chromatographic separation was performed in a Shim-pack® RP-18 column; the mobile phase comprising a mixture of 0.3% triethylamine (pH adjusted to 6.0 with 20% formic acid) and acetonitrile (66:34, v/v) at a flow-rate of 1.0 mL min-1 with isocratic elution. The temperature was set at 25 °C in the column oven. Bilastine was determined by UV detection at 207 nm using photodiode-array. The results demonstrated that the photodegradation kinetics of bilastine in methanolic solution follows the first order of reaction, with a t90% of 27.11 minutes and degradation rate constant (k) of 0.0007 min-1.